Post-pandemic face-to-face learning: Perspectives from physical education teachers - Kurniawan, Wahyu Ragil; Hartono, Mugiyo; Wijayanti, Dwi Gansar Santi (Journal Sport Area, 2023)
Returning to the face-to-face learning system for physical education, the researchers got several responses and responses from the stakeholders, one of which was the teacher. The purpose of this study was to determine the perceptions of physical education teachers in carrying out face-to-face learning activities in the post-pandemic. The method used is descriptive quantitative research. Data collection was carried out using a list of main questions that were used to guide this research, one of which was, "How do teachers respond to the return of the face-to-face system after the pandemic, which requires students to return to school to attend physical education directly?" The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of this study found one point that represents the response of teachers' perceptions about the advantages and disadvantages of learning activities from their point of view in conceptualizing the offline physical education learning approach by paying attention to identical prevention patterns in the post-pandemic period. The conclusions of this study indicate that teachers have a variety of views that contain elements of strengths and weaknesses in carrying out physical education learning activities with a face-to-face system after spending a long time during the pandemic using an online system. Next, the researcher's suggestion for further research is that a special study can be carried out on how to design a learning approach that is relevant to the post-pandemic conditions of physical education in elementary schools.